Nonlinear Deformation Analysis of Compressed Reinforced Concrete Elements of Circular Cross-section - Hajiyeva , U.M. (Herald of Azerbaijan Engineering Academy, 2021)
The creep of concrete plays an important role in the formation of the stress-strain state of reinforced concrete elements. The creep of concrete strongly affects the bearing capacity of compressed reinforced concrete elements. In the article, taking into account the nonlinearity of instantaneous and long-term deformations, an effective numerical method is developed for calculating compressed reinforced concrete elements of circular crosssection. For this purpose, a discrete analogue of the nonlinearly hereditary concrete creep equation was first constructed. When solving special relaxation problems, the high accuracy of the proposed discrete analog is shown. In long-term loadings the solution of the considered problem is reduced to the solution of a nonlinear system of algebraic equations. A numerical algorithm for solving the resulting nonlinear system with any desired accuracy is proposed, and the effectiveness of the proposed algorithm is proved in numerical examples.